Orientation-selective and directional deep brain stimulation in swine assessed by functional MRI at 3T - Slopsema, Julia P; Canna, Antonietta; Uchenik, Michelle; Lehto, Lauri J; Krieg, Jordan; Wilmerding, Lucius; Koski, Dee M; Kobayashi, Naoharu; Dao, Joan; Blumenfeld, Madeline; Filip, Pavel; Min, Hoon-Ki; et al. (Neuroimage, 2021)
Functional MRI (fMRI) has become an important tool for probing network-level effects of deep brain stimulation (DBS). Previous DBS-fMRI studies have shown that electrical stimulation of the ventrolateral (VL) thalamus can modulate sensorimotor cortices in a frequency and amplitude dependent manner. Here, we investigated, using a swine animal model, how the direction and orientation of the electric field, induced by VL-thalamus DBS, affects activity in the sensorimotor cortex. Adult swine underwent implantation of a novel 16-electrode (4 rows x 4 columns) directional DBS lead in the VL thalamus. A within-subject design was used to compare fMRI responses for (1) directional stimulation consisting of monopolar stimulation in four radial directions around the DBS lead, and (2) orientation-selective stimulation where an electric field dipole was rotated 0°-360° around a quadrangle of electrodes. Functional responses were quantified in the premotor, primary motor, and somatosensory cortices. High frequency electrical stimulation through leads implanted in the VL thalamus induced directional tuning in cortical response patterns to varying degrees depending on DBS lead position. Orientation-selective stimulation showed maximal functional response when the electric field was oriented approximately parallel to the DBS lead, which is consistent with known axonal orientations of the cortico-thalamocortical pathway. These results demonstrate that directional and orientation-selective stimulation paradigms in the VL thalamus can tune network-level modulation patterns in the sensorimotor cortex, which may have translational utility in improving functional outcomes of DBS therapy.
Keywords: Magnetic Resonance Imaging; Ventral Thalamic Nuclei; magnetická rezonanční tomografie; nuclei ventrales thalami; motorické korové centrum; Deep Brain Stimulation; Thalamus; Electric Stimulation; Female; nucleus subthalamicus; zvířata; Swine; thalamus; nervové dráhy; ženské pohlaví; Neural Pathways; hluboká mozková stimulace; Motor Cortex; Subthalamic Nucleus; Animals; elektrická stimulace; prasata